tDCS over the left prefrontal Cortex improves mental flexibility and inhibition in geriatric inpatients with symptoms of depression or anxiety: A pilot randomized controlled trial - Figeys, Mathieu; Villarey, Sheryn; Leung, Ada W. S.; Raso, Jim; Buchan, Steven; Kammerer, Hubert; Rawani, David; Kohls-Wiebe, Megan; Kim, Esther S. (Frontiers in Rehabilitation Sciences, 2022)
Background: Patients with depression and/or anxiety are commonly seen in inpatient geriatric settings. Both disorders are associated with an increased risk of cognitive impairments, notably in executive functioning. Transcranial direct current stimulation (tDCS), a type of non-invasive brain stimulation, involves the administration of a low-dose electrical current to induce neuromodulation, which ultimately may act on downstream cognitive processing. Objective: The purpose of this study was to determine the effects of tDCS on executive functioning in geriatric inpatients with symptoms of depression and/or anxiety. Design: Pilot Randomized Controlled Trial. Setting: Specialized geriatric wards in a tertiary rehabilitation hospital. Methods: Thirty older-aged adults were recruited, of which twenty completed ten-to-fifteen sessions of 1.5 mA anodal or sham tDCS over the left dorsolateral prefrontal cortex. Cognitive assessments were administered at baseline and following the tDCS protocol; analyses examined the effects of tDCS on cognitive performance between groups (anodal or sham tDCS). Results: tDCS was found to increase inhibitory processing and cognitive flexibility in the anodal tDCS group, with significant changes on the Stroop test and Trail Making Test-Part B. No significant changes were observed on measures of attention or working memory. Discussion: These results provide preliminary evidence that tDCS-induced neuromodulation may selectively improve cognitive processing in older adults with symptoms of depression and/or anxiety. Clinical Trials Registration: www.clinicaltrials.gov, NCT04558177 Funding: This work was supported by the Centre for Aging + Brain Health Innovation and the Glenrose Rehabilitation Hospital Foundation.